Multidimensional Poverty among Urban Refugees in Kenya during the COVID-19 Pandemic - Molelekoa, Thonaeng Charity; Oyekale, Abayomi Samuel (Acta Universitatis Danubius. Œconomica, 2025)
Poverty is a major problem among refugees and a proper understanding of its correlates is a fundamental requirement for policy interventions. This paper adds to existing body of knowledge by using the multidimensional poverty framework to analyse correlates of multiple deprivations among urban refugees in Kenya during the COVID-19 pandemic. The data were collected with telephone interviews from refugees from Mombasa, Nairobi and Nakuru. The Alkire-Foster approach to multidimensional poverty indicator (MPI) computation was used with twenty-eight welfare attributes. The correlates of the MPIs were further analysed with Tobit regression. The results showed that among housing characteristics, refugees showed the highest deprivations in ran out of water, cooking fuel and number of rooms, while the least among assets were smart phone and mattress ownership. Average MPI for all respondents was 0.5487, while Nairobi had the highest MPI (0.5597). The significant correlates of MPI (p<0.05) were memberships of Community-Based Organizations (CBOs) (-0.010283), residence in Nairobi (0.0244818), bank savings (0.0797315), MPESA savings (-0.036748), pillow savings (-0.034977), residence of foster child (-0.0216316), physical disability (0.0256857), serious medical problem (-0.0193773), formal borrowing (-0.0210615) and sold more animals (0.052714). The findings have underscored the magnitude of multidimensional poverty among urban refugees during the COVID-19 pandemic with emphases on promotion of membership in CBOs, savings, effective safety net to absorb income shocks and preferential poverty reducing interventions among disabled refugees.